Simultaneous two-stage surgical treatment for Chiari malformation association with occlusive hydrocephalus: a clinical case - D. D. Kositov; Kh. J. Rahmonov; R. N. Berdiev; Sh. A. Turdiboev; M. V. Davlatov; U. Kh. Rahmonov (Сеченовский вестник)
Treatment of patients with the simultaneous presence of Chiari malformation type I (MC I) and hydrocephalus may include both one-stage and two-stage surgical interventions. The article describes the two-stage surgical treatment experience performed for the first time in the Republic of Tajikistan.   Description of the case. A 50-year-old female patient with a three-year history of bursting headache, dizziness, nausea, and vomiting developed impaired coordination of movements and decreased visual acuity. Computed tomography (CT) revealedsigns of MC I: descent of the cerebellar tonsils 5 mm below the level of the foramen magnum and occlusive triventricular hydrocephalus with symmetrical enlargement of the lateral and third ventricles. The patient underwent surgery – endoscopic third ventriculocisternostomy (ETV) in combination with decompressive suboccipital craniectomy, which was supplemented by CI laminectomy. After the surgery, the symptoms regressed. According to the control CT scan, there was a moderate decrease in the size of the lateral and third ventricles, restoration of the normal anatomical structure of the posterior cranial fossa.